“Can You Listen to My Voice?” Including a Student Voice in the Design of a Chemistry Module Aiming to Increase Students’ Learning and Motivation - Kyza, Eleni A.; Georgiou, Yiannis (My University, 2014)
Science education has been criticized for failing to motivate young learners to learn science. This could be partially attributed to that even though curricula are designed for students, students’ views are often excluded from the curriculum design process. However, even though listening to students’ voices may result to more effective science curricula, such an approach has been barely practiced and has not received much empirical exploration. This work reports on a case study examining the development of inquiry-based module; participants included nine high school chemistry teachers (members of the PROFILES Cyprus 2012-13 professional development program) and their students who were consulted on their views regarding an ideal learning environment. The participatory design process adopted consisted of three separate parts: (a) the collection and analysis of students’ perspectives, (b) the development of the inquirybased learning environment based on students’ views and (c) the implementation and evaluation of the learning environment. Empirical evidence indicates that the designed learning environment, which took students’ perspectives into account, resulted to substantial learning gains in terms of increased conceptual understanding and motivation.
Keywords: Development of inquiry-based module; Science education; High school chemistry teachers; Students